Uji Mann-Whitney Perbedaan Harapan Lama Sekolah antara Provinsi Sumatera Selatan dengan Aceh Tahun 2023 - Ghea Putri Amalia P; Suliadi (UNISBA Press, 2024)
Abstract. Inferential statistics are often referred to as inductive statistics which are statistics used to analyse sample data and the result will be generalised or concluded for the population from which the sample was taken. Inferential statistics are categorised into two, namely parametric statistics and nonparametric statistics. One of the test used on two independent samples is the Mann-Whitney Test. The Mann-Whitney test can be used when the data is not normally distributed. The advantage of the Mann-Whitney test is that it can be used if the number of each sample is not the same. Expected Years of Schooling (EYS) is defined as the years of schooling (in years) that a child is expected to experience at a certain age in the future. It is assumed that the probability that the child will remain in school at subsequent ages is equal to the probability of the population being in school per the current population of the same age. Expected years of schooling are calculated for the population aged seven years and above. Hypothesis testing using the Mann-Whitney test shows that there is a significant difference between the expected years of schooling of districts/cities in South Sumatra Province and the expected years of schooling of districts/cities in Aceh Province in 2023. Abstrak. Statistika inferensial sering disebut sebagai statistika induktif yang merupakan statistik yang digunakan untuk menganalisis data sampel dan hasilnya akan digeneralisasikan atau disimpulkan untuk populasi dari asal sampel itu diambil. Statistika inferensial dikategorikan menjadi dua, yaitu statistika parametrik dan statistika nonparametrik. Salah satu pengujian yang digunakan pada dua sampel saling bebas ada Uji Mann-Whitney. Uji Mann-Whitney dapat digunakan ketika data tidak berdistribusi normal. Kelebihan dari uji Mann-Whitney yaitu bisa digunakan jika jumlah masing-masing sampel tidak sama. Harapan Lama Sekolah (HLS)/Expected Years of Schooling (EYS) didefinisikan lamanya sekolah (dalam tahun) yang diharapkan akan dirasakan oleh anak pada umur tertentu di masa mendatang. Diasumsikan bahwa peluang anak tersebut akan tetap bersekolah pada umur-umur berikutnya sama dengan peluang penduduk yang bersekolah per jumlah penduduk untuk umur yang sama saat ini. Angka harapan lama sekolah dihitung untuk penduduk berusia tujuh tahun ke atas. Uji hipotesis menggunakan uji Mann-Whitney menunjukkan bahwa terdapat perbedaan yang signifikan antara harapan lama sekolah kabupaten/kota di Provinsi Sumatera Selatan dengan harapan lama sekolah kabupaten/kota di Provinsi Aceh tahun 2023.